PENINGKATAN KESADARAN EKONOMI BERKELANJUTAN PEDAGANG KAKI LIMA MELALUI AKUNTANSI LINGKUNGAN DI PANTAI KUTA LOMBOK TENGAH - Widiya Pratiwi; Luh Utami; Rini Yuliandari; Baiq Silvi (LPPM Institut Pendidikan Nusantara Global, 2025)
Coastal tourism areas are vulnerable to environmental degradation due to intensive economic activities, particularly those conducted by street vendors. One of the main problems is inadequate business waste management and the low level of understanding of environmental accounting. This community service activity aims to increase the sustainable economic awareness of street vendors through the socialization of environmental accounting and waste management in the coastal area of Kuta Beach, Central Lombok. The methods used include socialization, interactive discussions, simple assistance in recording environmental costs, and evaluation through pre-tests and post-tests. The results show a significant improvement in participants’ understanding of environmental accounting concepts, waste segregation, and the relationship between environmental cleanliness and business sustainability. This activity contributes to supporting the development of sustainable coastal tourism through the application of environmental accounting in micro-enterprises within the informal sector.